Prognostic value of RDW at admission in patients with acute myocardial infarction - Berekat, Lewand Ibrahim; Jahjah, Akram; Alshemali, Suzanne (Journal of medical and pharmaceutical sciences, 2022)
Objective: The aim of this study is to evaluate the effect of basal RDW value on the in-hospital prognosis (mortality, complications) in patients with acute myocardial infarction, in addition to comparing the prognostic value of RDW in patients with acute myocardial infarction with other laboratory indicators, and the relation between RDW and Global Registry of Acute Coronary Events GRACE score and progression of heart failure and Length of hospitalizationMethods: a study applyed applied at Tishreen University Hospital in Lattakia-Syria during the period between February 2020-February 2021. The study included 145 acute myocardial infarction patients , and determination of the RDW value to study its effect on the prognostic of in-hospital mortality and complications.Results: A higher RDW value at admission was associated with higher rates of major cardiac complications such as cardiogenic shock (P = 0.007) and, arrhythmias (P = 0.0001) and a higher RDW value was associated with increased length of hospital stay (P = 0.01) and an increased death rate (P = 0.001). The statistically significant variables were entered into the logistic regression equation to identify the independent indicators for the warning of death within the hospital. We found that the high level of RDW is a prognostic biomarker of death in hospital (OR = 4.1, P = 0.0001), in addition to that in the case of previous coronary or peripheral vascular diseases (OR = 3.8, P = 0.006), lower EF (OR = 2.8, P = 0.001) and higher GRACE score (OR = 3.1, P = 0.002).Conclusion: In patients with acute myocardial infarction, high RDW has an independent predictive value for death, cardiogenic shock, and arrhythmias during hospitalization.
Keywords: Red Blood Cells; myocardial; infarction; Arrhythmia; Heart Failure